Description of a new species and two new records of the family Cosmopterigidae (Lepidoptera) from Korea - Kim, So-Yeon; Sinev, Sergey Yu.; Byun, Bong-Kyu (Zootaxa, 2024)
Three species belonging to the family Cosmopterigidae are treated: Anatrachyntis koreana sp. nov. is described as new to science, Anatrachyntis ptilodelta (Meyrick, 1922) and Macrobathra nomaea Meyrick, 1914 are reported for the first time in Korea. The illustrations of the adults and genitalia of all treated species are provided.